Terms of staff of higher educational institutions - Демченко, Яна Анатоліївна (Educological discourse, 2013)
The research conducted by us confirms a hypothesis that training to use modern multimedia means and development of presentation competence can be one of the basic directions of development of teachers and the university personnel as a whole. Leading positions are occupied with university which has the modern equipment and technologies, and creates system of development of modern methods employees, applying thus approaches to the personnel development, borrowed in business.